East Asian monsoon changes early in the last deglaciation and insights into the interpretation of oxygen isotope changes in the Chinese stalagmite record. (15th December 2020) - Liang, Yijia; Zhao, Kan; Edwards, R. Lawrence; Wang, Yongjin; Shao, Qingfeng; Zhang, Zhenqiu; Zhao, Bin; Wang, Quan; Cheng, Hai; Kong, Xinggong
Abstract: Stalagmite oxygen isotope (δ 18 O) records have enhanced our understanding of the history of the East Asian monsoon. However, abrupt changes in the monsoon are not constrained well enough to address certain issues and there are still unknowns in the interpretation of cave δ 18 O records. Here we present a new high-resolution stalagmite record from Shima Cave, central China. Anchored with 24 230 Th/U dates, our sample grew from 19.7 to 17.8 ka and from 16.3 to 13.3 ka, covering much of the early portion of the last deglaciation with a temporal resolution of 7 years. Using this record and other available Asian δ 18 O records, we test model predictions for shifts in δ 18 O in Asian caves and further investigate monsoon variations on centennial to decadal timescales during the early portion of the last termination. We conclude the following regarding the interpretation of δ 18 O in Chinese caves. Two mechanisms affect δ 18 O: changes in the fraction of monsoon rainfall in annual totals (the Wang-Cheng mechanism) and changes in the amount of rainout between tropical sources and cave sites (the Yuan mechanism). The former is caused by changes in the seasonal migration of the sub-tropical jet and likely has a smaller effect on cave δ 18 O than the latter. The latter involves changes in rainout from both the Pacific and the Indian Ocean sources. Precisely how that change in rainout is partitioned between sources and cave sites is not fully understood; however, it is clear that some of the change takes place in China; i.e. it is not restricted to upstream sites. Rough calculations for our site suggest that mean annual rainfall may have been two-thirds of modern values at the time of the highest δ 18 O values during Heinrich Stadial 1 (HS1) (16.1 ka) and one fifth again higher than modern values during the Bølling (14.3 ka). Within HS1, consistent with observations from other localities, Chinese cave records exhibit a twofold structure. Within the phases, we observe a truly remarkable relationship between the North Atlantic ice rafted debris record and the Hulu-Shima Cave record, where events ranging from multi-centennial to sub-decadal timescale can be related across Eurasia. The origin of this two-phased structure may relate to different sources and extent of ice-rafted debris in the North Atlantic as well as the extent of sea ice and the Atlantic Meridional Overturning Circulation. Highlights: Two mechanisms affect Chinese stalagmite δ 18 O: the Wang-Cheng mechanism and the Yuan mechanism. A two-phased structure of East Asian Monsoon during Heinrich Stadial 1, an early weakening and a subsequent weaker condition. A remarkable relationship between ice-rafting events and weak monsoon events on the multi-centennial to sub-decadal scale.